Bachelors, manhood, and the novel, 1850-1925 - Snyder, Katherine V. (Cambridge, U.K. ; New York : Cambridge University Press, 1999)
"Katherine Snyder's study explores the significance of the bachelor narrator, a prevalent but little recognized figure in premodernist and modernist fiction by male authors, including Hawthorne, James, Conrad, Ford, and, Fitzgerald. Snyder demonstrates that bachelors functioned in cultural and literary discourse as threshold figures who, by crossing the shifting, permeable boundaries of bourgeois domesticity, highlighted the limits of conventional masculinity. The very marginality of the figure, Snyder argues, effects a critique of gendered norms of manhood, while the symbolic function of marriage as a means of plot resolution is also made more complex by the presence of the single man. Bachelor figures made, moreover, an ideal narrative device for male authors who themselves occupied vexed cultural positions."--Jacket
Trouble in paradise: bachelors and bourgeois domesticity -- Susceptibility and the single man: the constitution of the bachelor invalid -- Artist and a bachelor: Henry James, mastery and the life of art -- Way of looking on: bachelor narration in Joseph Conrad's.
Based on the author's thesis (Ph. D.)--Yale University.
Includes bibliographical references (pages 258-278) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Conrad, Joseph, -- 1857-1924 -- Characters -- Bachelors; James, Henry, -- 1843-1916 -- Characters -- Bachelors; Conrad, Joseph, -- 1857-1924; James, Henry, -- 1843-1916; Conrad, Joseph, -- (1857-1924) -- Personnages -- Hommes seuls; James, Henry, -- (1843-1916) -- Personnages -- Hommes seuls; Conrad, Joseph; James, Henry; American fiction -- Male authors -- History and criticism; Bachelors in literature; American fiction -- 19th century -- History and criticism; English fiction -- 20th century -- History and criticism; English fiction -- Male authors -- History and criticism; English-speaking countries -- Intellectual life -- 19th century; Masculinity in literature; First person narrative; Men in literature; Célibataires dans la littérature.; Roman américain -- 19e siècle -- Histoire et critique; Roman anglais -- 20e siècle -- Histoire et critique; Masculinité dans la littérature.; Narration à la première personne; Hommes dans la littérature.; LITERARY CRITICISM -- American -- General; American fiction; American fiction -- Male authors; Bachelors in literature; English fiction; English fiction -- Male authors; First person narrative; Intellectual life; Masculinity in literature; Men in literature; English-speaking countries; Lediger; Erzähler; Lediger; Literatur; Roman; USA; Ongehuwden; Mannelijkheid; Romans; Engels; Amerikaans; Hommes seuls -- Dans la littérature.; Masculinité (psychologie) -- Dans la littérature.; Geschichte 1850-1925.; Geschichte 1850-1930.; Englisch; 1800-1999; Criticism, interpretation, etc